Penyuluhan Kepada Masyarakat Desa Sumberejo Tentang Kemudahan Konsultasi Kesehatan Secara Online Melalui Aplikasi Alodokter - Mar’atus Sholikhah; Aufa Izzuddin Baihaqi (Universitas Katolik Widya Karya Malang, 2023)
Easy access to health information and consultation is important in improving the quality of life and welfare of the community. Currently, a digital health application has emerged that allows the public to get quick and easy access to health information and to conduct online consultations with medical personnel. One popular application is Alodokter, which provides online health consultation services via mobile devices. The purpose of this study is to provide counseling to the people of Sumberejo Village about the convenience of online health consultations through the Alodokter application. This research was conducted using qualitative research methods with an observational study approach. The counseling technique is carried out using a combination of lecture techniques and demonstrations using the Alodokter application. Through this counseling, the public can understand and know how to use the Alodokter application as a means to obtain health information and conduct medical consultations online